Preliminary Study: Detection of Ecto and Endoparasites Among Wild Rats From Urban Area in Blimbing, Malang, East Java - shelly kusuma; Reza Yesica; Ida Bagus Gde Rama Wisesa; Jenny Hermanto; Yustia Nurholizah; Maria Widyaneni Trinastuti (Acta VETERINARIA Indonesiana, 2021)
Zoonotic parasitic infections is one of the global public health issues. The complex parasite transmission allows for the relationship between people, animals, vectors, and the environment. The existence of rat in the environment has an important role as a host and reservoir for various types of ecto and endoparasites. This study was conducted to collect informative data on the parasitic infection of wild rats in Blimbing sub-district, Malang city, East Java. A total number of eight wild rat were captured using live-traps from landfills during 4 days. They were classified by sex, weight and body length. The rats were anesthetized, collecting for any ectoparasites and then their carcasses were dissected for examinations of endoparasites. The result of this study show succesfull live-trap of rodents including Rattus norvegicus (87.5%) and Suncus murinus (12.5%). 50% of sampled rodents were male, 37.5% were female, and 12.5% of female the musk shrew. The presence of helminthes infection in all wild rats, namely Hymenolopis nana, Syphacia obvelata, Nippostrongylus brasiliensis. Furthermore, the ectoparasites identification were Xenopsylla cheopis, Echinolaelap echidninus, and blood protozoa identifications Trypanosoma lewisi. Based on the results show 100% of wild rats positive infections of endo-ectoparasites. This study indicates to continuous study among rodents’ parasites in wild rats in different urban areas and analysis of their potential impact on public health.